Information System for the Governance of University Cooperation - Laaziri, M.; Khoulji, S.; Benmoussa, K.; Larbi, K. M. (Engineering, Technology & Applied Science Research, 2018)
Recognizing the impact of international cooperation in science and technology, all higher education institutions prioritize strategic partnerships. If setting up a partnership is important, its management, monitoring and evaluation of cooperation actions, regular communication among partners, and the ability to allow all parties to monitor the functioning of the partnership are more important. For good co-operation management, an information system becomes a mandatory condition. Abdelmaleek Essaadi’s University team has set up an information system for the governance of a university cooperation called SIMACoop, to support cooperation between governments and universities, and to facilitate the process of partnership management. This system also helps in identifying the shared vision and goals of the partnership members and develops documents that define the partnership terms. In addition, SIMACoop has put in place procedures for maintaining and monitoring the partnership evolution [1]. The purpose of this article is to give a general presentation on SIMACoop’s design and development for the governance of university cooperation.